After the death march: Everyday life of Filipino prisoners of war in Camp O'Donnell (1942-1943) - Abellar, Mark Kevin P. (Animo Repository, 2022)
Filipino soldiers were accustomed to their ordinary lives prior to the outbreak of World War II; however, everything changed as their everyday life would be taken away as they entered a new life as a prisoner of war. This study looks at the daily lives of Filipino POWs imprisoned at Camp O’Donnell from 1942 to 1943. It also examines the mental state of Filipino soldiers as well as the conditions they encountered in the prison camp. Using a social history perspective, the study is anchored on the Everyday Life of Filipino POWs in Camp O’Donnell. According to Andreas Eckert and Adam Jones’ article, Everyday Life includes actions that can be classified as ‘routine,’ attitudes that can be classified as ‘mental habits.’ And rituals that refer to special occasions in the lives of individuals and communities (Eckert & Jones, 2016). Specifically, it includes the following categories: basic needs, health issues, work and livelihood, transportation and communication, leisure and recreation, and interpersonal relationships (Kintanar, 2016). The study used the historical method, that is, the descriptive-narrative-analytical method, adapted from M.C. Lemon’s History of Philosophy, to follow a Filipino narrative (Lemon, 2003). The study found that, during confinement, the Filipino POWs adapted to the harsh conditions of the prison camp despite a lack of basic necessities. One of these was their camaraderie with one another, which greatly contributed to their mental strength. Furthermore, they created a new life that perpetrated the life they had prior to the war. This was done to instill a sense of normalcy so that their conditions in the camp will not be too punishing. Keywords: Camp O'Donnell, Filipino Prisoners of War, World War II, Everyday Life, Tarlac.